O'Reilly Strata Data Conference 2019, New York, New York - O'Reilly Strata Data Conference (2019, New York, N.Y.) ([Place of publication not identified] O'Reilly Media, 2019)
"The 2019 Strata Data Conference NYC, the biggest Big Data conference in the world, was a massive success. Packed with thousands of attendees, Strata gathered the world's top data practitioners to provide expert guidance on the tools and technologies you need to make your data strategies and projects work today. This video compilation holds the best of Strata NYC 2019's keynotes, tutorials, and technical sessions. Looking for a head start on the data techniques and technologies you need to succeed? This compilation points the way forward by offering you hours of material to study and absorb at your own rate. The compilation includes such gems as Data Engineering and Architecture sessions, where you'll learn how to select the right type of data infrastructure and architecture to streamline your workflows, reduce costs, and scale your data analysis; Data Science, Machine Learning (ML) and AI sessions, where you'll learn how to use text mining, real-time analytics, large-scale anomaly detection and other techniques to discover the hidden insights in your data; and all of the best talks from the Strata Business Summit, where you'll receive an insiders-only look at the processes and technologies some of the world's most successful companies used to develop their own data strategies."--Resource description page
Title from resource description page (Safari, viewed January 29, 2020)
Keywords: Data structures (Computer science) / Congresses; Structures de données (Informatique) / Congrès; Artificial intelligence / Congresses; Intelligence artificielle / Congrès; Electronic data processing / Congresses; Artificial intelligence / fast / (OCoLC)fst00817247; Cloud computing / Congresses; Electronic data processing / fast / (OCoLC)fst00906956; Infonuagique / Congrès; Data structures (Computer science) / fast / (OCoLC)fst00887978; Cloud computing / fast / (OCoLC)fst01745899; O'Reilly Strata Data Conference / (2019 / New York, N.Y.)